2008
DOI: 10.1152/ajpheart.00796.2007
|View full text |Cite
|
Sign up to set email alerts
|

Effective arterial elastance as an index of pulmonary vascular load

Abstract: Morimont P, Lambermont B, Ghuysen A, Gerard P, Kolh P, Lancellotti P, Tchana-Sato V, Desaive T, D'Orio V. Effective arterial elastance as an index of pulmonary vascular load. Am J Physiol Heart Circ Physiol 294: H2736-H2742, 2008. First published April 18, 2008 doi:10.1152/ajpheart.00796.2007.-The aim of this study was to test whether the simple ratio of right ventricular (RV) endsystolic pressure (Pes) to stroke volume (SV), known as the effective arterial elastance (E a), provides a valid assessment of pulm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 27 publications
3
58
0
3
Order By: Relevance
“…To the best of our knowledge, this is the first report of a strong relationship between contractile reserve and resting ventricular-arterial coupling in an experimental model of RV dysfunction. Several studies have previously demonstrated that functional changes during exercise are adaptive if the ventricle is energetically efficient, which is usually observed with an Ees/Ea ratio of 1-2 [17,18]. Our findings are in accordance with studies showing that patients with PH have an impairment of power transfer and ventricular efficiency during exercise [11,19].…”
Section: Discussionsupporting
confidence: 92%
“…To the best of our knowledge, this is the first report of a strong relationship between contractile reserve and resting ventricular-arterial coupling in an experimental model of RV dysfunction. Several studies have previously demonstrated that functional changes during exercise are adaptive if the ventricle is energetically efficient, which is usually observed with an Ees/Ea ratio of 1-2 [17,18]. Our findings are in accordance with studies showing that patients with PH have an impairment of power transfer and ventricular efficiency during exercise [11,19].…”
Section: Discussionsupporting
confidence: 92%
“…It has been suggested that subtraction of left atrial (or pulmonary capillary wedge pressure) gives a better estimate of R5Ea6T [34]. However, it has not been shown which estimate of Ea is best for estimation of coupling (i.e.…”
Section: Possible Limitations Of the Proposed Methodsmentioning
confidence: 99%
“…First, in the datasets, pulmonary artery pressure is particularly low, sometimes even negative, as previously mentioned. Second, in the case of the pulmonary circulation, downstream pressure cannot be neglected with respect to pulmonary artery pressure [20]. Equation (14) cannot be further simplified to R pul ≈P pa /CO.…”
Section: Other Parameter Valuesmentioning
confidence: 99%